Tool to monitor tobacco control policy implementation: the Tobacco Control Scale in Latin America. Adaptation process and pilot study - Ariadna Feliu; Cristina Martinez; PERUGA URREA, ARMANDO; Luk Joossens; Eduardo Bianco; Marco Cornejo; Sarah O Nogueira; Esteve Fernández (My University, 2021)
BackgroundMonitoring tobacco control policy implementation is one of the keys for tobacco consumption reduction in Latin America (LA). This study reports on the adaptation of the Tobacco Control Scale (TCS) for use in LA countries and the level of tobacco control policy implementation in this region according to the scale.MethodsEcological cross-sectional survey. The questionnaire to measure tobacco control policies was a translated (into Spanish and Portuguese) and adapted version of the last TCS as used in Europe. The resulting TCS-LA maintains the same structure as the original TCS, with eight policy domains and 100 points (pts) as maximum score; however, four policy domains were adapted because the exact same rationale could not be applied. At least two non-governmental tobacco control experts were contacted per country to answer the TCS-LA.ResultsInformants from 17 out of 18 countries completed the questionnaire. Using the TCS-LA, Panama (70 pts), Uruguay (68 pts) and Ecuador (61 pts) exhibited the strongest tobacco control policies, while Guatemala (32 pts), Bolivia (30 pts) and Dominican Republic (29 pts) have implemented a lower number of tobacco control policies. Eight countries reached 50% of the TCS-LA total possible score, indicating a relatively good implementation level of tobacco control policies.ConclusionsPanama, Uruguay and Ecuador are the tobacco control policy leaders in LA; however, tobacco control in the region has room for improvement since nine countries have a total score under 50 pts. The TCS is a feasible and adaptable tool to monitor tobacco control in other WHO regions beyond Europe.
Keywords: public policy; surveillance and monitoring; global health; cross-sectional studies; health policy; humans; latin america; pilot projects; tobacco; tobacco use; article; bolivia; dominican republic; ecuador; europe; global health; guatemala; human; human experiment; leadership; panama; pilot study; public policy; questionnaire; tobacco; uruguay; cross-sectional study; health care policy; pilot study; prevention and control; south and central america; tobacco use